2017
DOI: 10.1371/journal.pone.0175096
|View full text |Cite
|
Sign up to set email alerts
|

Depression, distress and self-efficacy: The impact on diabetes self-care practices

Abstract: The prevalence of type 2 diabetes is increasing in Malaysia, and people with diabetes have been reported to suffer from depression and diabetes distress which influences their self-efficacy in performing diabetes self-care practices. This interviewer administered, cross sectional study, conducted in the district of Hulu Selangor, Malaysia, involving 371 randomly selected patients with type 2 diabetes, recruited from 6 health clinics, aimed to examine a conceptual model regarding the association between depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
83
3
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(107 citation statements)
references
References 57 publications
(61 reference statements)
13
83
3
8
Order By: Relevance
“…Although the association between diabetes distress and self‐efficacy was significant in the regression and correlation analysis, the current study showed that self‐efficacy played a completely mediating role in diabetes distress and self‐management behaviors. This was consistent with that of two previous studies suggesting that self‐efficacy mediates the association between diabetes distress and DSM behaviors (Devarajooh & Chinna, ; Lin et al., ). The main reason may be the influence of sociocultural norms on people's perception of disease.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Although the association between diabetes distress and self‐efficacy was significant in the regression and correlation analysis, the current study showed that self‐efficacy played a completely mediating role in diabetes distress and self‐management behaviors. This was consistent with that of two previous studies suggesting that self‐efficacy mediates the association between diabetes distress and DSM behaviors (Devarajooh & Chinna, ; Lin et al., ). The main reason may be the influence of sociocultural norms on people's perception of disease.…”
Section: Discussionsupporting
confidence: 93%
“…The results in the final model further confirmed that self‐efficacy was a strong predictor of DSM behaviors. This is consistent with the results of numerous prior investigations (Al‐Amer et al., ; Bhandari & Kim, ; Cosansu & Erdogan, ; Devarajooh & Chinna, ; Gao et al., ; Hu, Dong et al., ; Kav et al., ; Ku & Kegels, ; Lin et al., ; Walker et al., ; Yang et al., ; Yuan et al., ; Yue et al., ; Zhao et al., ; Zhong et al., ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A sense of high self-efficacy leads to greater effort, resilience, and flexibility. People with high self-efficacy feel more capable than those with poor self-efficacy (19). Also, self-efficacy affects one's healthy behaviors and the management of chronic diseases (20).…”
mentioning
confidence: 99%